2018
DOI: 10.1007/s12011-017-1239-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Copper and Zinc Supplementation on Weight Gain and Hematological Parameters in Pre-weaning Calves

Abstract: Cow-calf operations may be affected by trace mineral deficiencies, particularly copper (Cu) and zinc (Zn) deficiency, which may decrease the calf daily weight gain and alter hematological parameters. We evaluated the effect of Cu and Zn supplementation on pre-weaning calves (n = 40; 92 ± 6 kg initial body weight) from the Salado River basin, Buenos Aires, Argentina. Calves were divided into four groups (n = 10 each) and subcutaneously administered 0.3 mg/kg Cu (Cu group), 1 mg/kg Zn (Zn group), Cu and Zn toget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
2
7
0
2
Order By: Relevance
“…At present, 2 principal forms of zinc are used: inorganic zinc sources, such as zinc oxide (ZnO), and organic zinc sources, such as zinc methionine (Zn-Met). Zinc oxide, especially when administered at a high dose, promotes growth and immunity and reduces the incidence of diarrhea (Fairbrother et al, 2005;Pettigrew, 2006;Mattioli et al, 2018). Furthermore, some research has shown that an appropriate amount of ZnO increases the relative abundance of Escherichia coli (Bednorz et al, 2013) but decreases that of Lactobacillus in the gut of weaned piglets (Hojberg et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…At present, 2 principal forms of zinc are used: inorganic zinc sources, such as zinc oxide (ZnO), and organic zinc sources, such as zinc methionine (Zn-Met). Zinc oxide, especially when administered at a high dose, promotes growth and immunity and reduces the incidence of diarrhea (Fairbrother et al, 2005;Pettigrew, 2006;Mattioli et al, 2018). Furthermore, some research has shown that an appropriate amount of ZnO increases the relative abundance of Escherichia coli (Bednorz et al, 2013) but decreases that of Lactobacillus in the gut of weaned piglets (Hojberg et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The liver, in particular, is the major storage organ of Cu and Zn, and the stored Cu is largely bound to the metallothionein in most species, which have the capacity to bind both physiological (such as zinc, copper, and selenium) and xenobiotic (such as cadmium, mercury, silver, and arsenic) heavy metals through the thiol group of its cysteine residues [44,45]. The blood biochemical variables of calves were improved under Zn and Cu administration [6,46].…”
Section: Discussionmentioning
confidence: 99%
“…Trace elements, especially copper (Cu) and zinc (Zn), have vital structural or catalytic roles in many metal-binding proteins and metalloenzymes, which are important for immune system function, nutrient metabolism [1][2][3], and health in rabbits; in addition, they had proven significant antimicrobial effect [4][5][6]. Pharmacological amounts of Zn and Cu, either incorporated into the diet or injected into the body, enhanced the growth performance of rabbits, particularly after/during the weaning stage [7].…”
Section: Introductionmentioning
confidence: 99%
“…Western blot samples were also used to assess intracellular Cu concentration, following established procedures [ 32 ]. In brief, the samples underwent acid digestion using a 3:1 mixture of nitric and hydrochloric acid.…”
Section: Methodsmentioning
confidence: 99%